Beilschmiedia danhkyii (Lauraceae), a new species from Vu Quang National Park, Vietnam - Quang, Bui Hong; Tagane, Shuichiro; Viet, Hung Nguyen; Canh, Toan Thai (Phytotaxa, 2021)
The new species Beilschmiedia danhkyii (Lauraceae) is described from Ha Tinh Province, Central Highland of Vietnam. Beilschmiedia danhkyii is characterized by ferruginous hairy terminal buds, branchlets and abaxial surfaces of lamina, subopposite leaves, adaxially impressed midrib and secondary veins, short inflorescence 2–3(–5) cm long, and large ellipsoid fruits 5–8 cm long, by which combination it is cleary distinguished from the other species of Beilschmiedia in the region. Taxonomic description, a table comparing morphological characters of the allied species, and color photo-plate are provided.